Hubungan Pengetahuan dengan Perilaku Pencegahan Penularan Covid-19 Pada Ibu Hamil - Fitria Nurwulansari; Solihah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2022)
Non-natural disasters caused by the Corona Virus or Covid-19 have spread and have an impact on maternal and child health problems. Covid-19 virus infection in pregnant women as a vulnerable group worsen the conditions of their pregnancy. Thus, an understanding of Covid-19 and its prevention is needed which will increase the awareness of pregnant women to take preventive measures against Covid-19. The purpose of this study was to analyze the relationship between knowledge and Covid-19 prevention behavior in pregnant women in the Independent Practice of Midwife "T" Bandung Regency. The research design was analytic observational using a cross-sectional approach which was carried out in 2020. The respondents were 55 pregnant women who were selected using a purposive sampling technique. The research instrument used a questionnaire to measure knowledge and behavior to prevent Covid-19. Data analysis were univariate analysis and bivariate analysis using chi square. The results showed that there was a significant relationship between knowledge and Covid-19 prevention behavior in pregnant women with a p-value (0.032) <0.05. Efforts are needed to increase awareness of pregnant women regarding the prevention of Covid-19 both during antenatal service and by developing education through various information media.